2018
DOI: 10.1038/s41388-017-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 inhibition alters the chemotherapy-driven rearrangement of the oncogenic secretome

Abstract: Adaptive resistance to therapy is a hallmark of cancer progression. To date, it is not entirely clear how microenvironmental stimuli would mediate emergence of therapy-resistant cell subpopulations, although a rearrangement of the cancer cell secretome following therapy-induced stress can be pivotal for such a process. Here, by using the highly chemoresistant malignant pleural mesothelioma (MPM) as an experimental model, we unveiled a key contribution of the chaperone HSP90 at assisting a chemotherapy-instigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Multiple different nuclear and cytoplasmic factors such as DNA damage, cytoplasmic chromatin fragments (CCFs), transposable elements, and toll like receptors (TLR) have been shown to trigger SASP. Different pathways such as p38MAPK (Freund et al, 2011), JAK2/STAT3 (Hubackova et al, 2010;Xu et al, 2015b), inflammasome (Acosta et al, 2013), mTOR (Herranz et al, 2015;Laberge et al, 2015), phosphoinositide-3-kinase (PI3K) pathway (Bent et al, 2016;Zhang et al, 2018), HSP90 (Di Martino et al, 2018), non-coding RNAs (Bhaumik et al, 2009;Yap et al, 2010;Puvvula et al, 2014;Panda et al, 2017;Baker et al, 2019;Barnes et al, 2019), GATA4/p62-mediated autophagy (Kang et al, 2015), macroH2A1 and ATM (Chen et al, 2015) are all involved in the development and regulation of SASP. It is dynamically and temporally, regulated at multiple different levels such as chromatin modification, transcription, secretion, mRNA stability and translation.…”
Section: Mechanisms Involved In the Dynamic Regulation Of The Senescementioning
confidence: 99%
“…Multiple different nuclear and cytoplasmic factors such as DNA damage, cytoplasmic chromatin fragments (CCFs), transposable elements, and toll like receptors (TLR) have been shown to trigger SASP. Different pathways such as p38MAPK (Freund et al, 2011), JAK2/STAT3 (Hubackova et al, 2010;Xu et al, 2015b), inflammasome (Acosta et al, 2013), mTOR (Herranz et al, 2015;Laberge et al, 2015), phosphoinositide-3-kinase (PI3K) pathway (Bent et al, 2016;Zhang et al, 2018), HSP90 (Di Martino et al, 2018), non-coding RNAs (Bhaumik et al, 2009;Yap et al, 2010;Puvvula et al, 2014;Panda et al, 2017;Baker et al, 2019;Barnes et al, 2019), GATA4/p62-mediated autophagy (Kang et al, 2015), macroH2A1 and ATM (Chen et al, 2015) are all involved in the development and regulation of SASP. It is dynamically and temporally, regulated at multiple different levels such as chromatin modification, transcription, secretion, mRNA stability and translation.…”
Section: Mechanisms Involved In the Dynamic Regulation Of The Senescementioning
confidence: 99%
“…Unfortunately, there is no research on the epigenetic control of secretome-associated chemoresistance in CSCs or in the total pool of the tumor population. Only one recent publication has related the inhibition of the HSP90 chaperone with a higher sensitivity to chemotherapy and a lower release of various cytokines (IL-8 and others) and, more interestingly, the HSP90 chaperone affected the survival of chemoresistant ALDH cell subpopulations [233]. In addition, there is little information available on oncogenic mutations associated with the influence of chemoresistance on CSC secretome, but p53 mutations have been reported to induce the release of an altered secretome by the tumor pool subpopulations that affects chemoresistance and other tumor processes [234,235].…”
Section: Secretome In Chemoresistancementioning
confidence: 99%
“…However, if the cancer cells were already p14ARF positive, indicating oncogene-induced senescence, increased cell death was observed when HSP90 was inhibited [50]. Recent studies also showed that inhibition of HSP90 altered the release of several cytokines in cancer cells from a protumorigenic secretome to a pro-apoptotic senescence status, thus resulting in chemosensitizing effects [51].…”
Section: Hsp90 Inhibitors As Senolyticsmentioning
confidence: 99%